1995
DOI: 10.1038/bjc.1995.3
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the p53 gene in human choriocarcinoma cell lines

Abstract: SummaryIn the present study. we analysed human choriocarcinoma cell lines for abnormalities in the tumour-suppressor gene p53 by Southern blotting, Northern blotting, non-radioisotopic single-stranded conformational polymorphism (SSCP) and complementary DNA sequencing. In all cell lines (Bewo, GCH-1, GCH-2. SCH, JAR, JEG-3. NUC-1 and HCCM-5), no p53 gene abnormality was detected by using Southern blotting. p53 mRNA of the expected size was detected in all cell lines tested by Northern blotting. SSCP analysis r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
158
0
2

Year Published

1997
1997
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(175 citation statements)
references
References 10 publications
12
158
0
2
Order By: Relevance
“…Consistently, LPA induces HIF-1␣ and VEGF expression in SK-Hep1 cells with wtp53 but not in p53-null Hep-3b cells (41,42). On the other hand, it is reported that LPA stimulated HIF-1␣ expression in ovarian OVCAR-3 and CAVOV-3 cells, despite the presence of mutp53 (41,43). The basis for the differential cellular responses by the different cell types is not known.…”
Section: Discussionmentioning
confidence: 98%
“…Consistently, LPA induces HIF-1␣ and VEGF expression in SK-Hep1 cells with wtp53 but not in p53-null Hep-3b cells (41,42). On the other hand, it is reported that LPA stimulated HIF-1␣ expression in ovarian OVCAR-3 and CAVOV-3 cells, despite the presence of mutp53 (41,43). The basis for the differential cellular responses by the different cell types is not known.…”
Section: Discussionmentioning
confidence: 98%
“…33 PA -1 ovarian tumor cells carry a silent mutation and are p53 wild -type. 31 MIAPaCa2 pancreatic tumor cells carry an Arg-to -Trp mutation in codon 248 of the p53 gene, an Arg -to -His mutation in codon 273 of the p53 gene, and express mutant p53. 32 …”
Section: Human Tumor Cell Linesmentioning
confidence: 99%
“…We observed that Ad-p53 22/23 failed to induce apoptosis in the Caov-3 cell line, but induced limited apoptosis in MDAH 2774 cell line (data not shown). Both ovarian cancer cell lines harbour p53 mutations (Yaginuma and Westphal, 1992). Therefore, p53 22/23 may still be able to induce apoptosis via a transcriptionindependent mechanism(s).…”
Section: Discussionmentioning
confidence: 99%